Shariah and legal aspects of creating a regulatory framework for Islamic banking in Maldives - Hassan, Abdullah Shiham (Ahmad Ibrahim Kuliyyah of Laws, International Islamic University Malaysia, 2009)
Prudential regulation and supervision of banks is just as necessary in an Islamic system as in conventional systems. However, given the fact that no "One-size fits all" countries with regard to creation of a regulatory framework for Islamic banking and finance, the "build-on as you go" policy would be the best policy for a country such as Maldives where attempts are being made for the first time to introduce of Islamic banking and finance as a parallel system to the conventional banking system that operated since 1974. First task of Maldives Monetary Authority as regulator and supervisor would be to take full consideration of the guidelines that have been already formulated by the standard setting bodies such as the Islamic Financial Services Board (IFSB) and Auditing and Accounting Organization for Islamic Financial Institutions (AAOIFI). This exercise would highlight Shari'ah and legal aspects of protecting specific risks associated with Islamic banking and finance. Second task for Regulator would be to determine whether to formulate a separate regulatory framework for Islamic banking or whether to follow the majority of jurisdictions where both Islamic and conventional banking operations have been governed by the same regulatory framework, reinforced by the compliance to the Shari'ah framework. Majority view is that regulators equipped with adequate regulatory tools ( disclosure, regulatory and prudential reporting, policy development capability, powers to inspect and investigation, combined with adequate powers of enforcement) should formulate an integrated regulatory structure with justified modifications to reflect the specificities of Islamic finance. Other view is that it is not obvious if there are any compelling reasons in favour of either of these two approaches. Hence, Regulator in Maldives may have to undertake a political and cultural balancing act in determining the regulatory structure that would be pragmatic and flexible enough to meet internationally accepted prudential and supervisory requirements, while at the same time is consistent with Islamic precepts.